Effects of trans-acting Genetic Modifiers on Meiotic Recombination Across the a1–sh2 Interval of Maize - Yandeau-Nelson, Marna D. (Copyright © 2006 by the Genetics Society of America, 2006)
Meiotic recombination rates are potentially affected by cis- and trans-acting factors, i.e., genotype-specific modifiers that do or do not reside in the recombining interval, respectively. Effects of trans modifiers on recombination across the ∼140-kb maize a1–sh2 interval of chromosome 3L were studied in the absence of polymorphic cis factors in three genetically diverse backgrounds into which a sequence-identical a1–sh2 interval had been introgressed. Genetic distances across a1–sh2 varied twofold among genetic backgrounds. Although the existence of regions exhibiting high and low rates of recombination (hot and cold spots, respectively) was conserved across backgrounds, the absolute rates of recombination in these sequence-identical regions differed significantly among backgrounds. In addition, an intergenic hot spot had a higher rate of recombination as compared to the genome average rate of recombination in one background and not in another. Recombination rates across two genetic intervals on chromosome 1 did not exhibit the same relationships among backgrounds as was observed in a1–sh2. This suggests that at least some detected trans-acting factors do not equally affect recombination across the genome. This study establishes that trans modifier(s) polymorphic among genetic backgrounds can increase and decrease recombination in both genic and intergenic regions over relatively small genetic and physical intervals.